Infrastructure for large-scale survey measurement: Cooperation between academic research and private-sector agencies - Peter Ph. Mohler; Bernhard von Rosenbladt (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
High-quality data from large-scale surveys provide a solid basis for outstanding research in the social sciences. Because of the unique demands of survey measurement in terms of the resources and skills required, it should be viewed as a specific sector of the research data infrastructure. In Germany, large-scale surveys have been established both within and outside academia, and major new projects are underway. Clearly, the sector is expanding. There is a need to discuss future challenges, not only with a focus on individual large projects, but with a view to the sector of large-scale survey measurement in general. One aspect is the segmentation of large-scale survey measurement in Germany along institutional lines (statistical offices, ministerial or government agency research (Ressortforschung), public research institutions, and the academic community). Here, we recommend that an overall framework be developed covering all sub-sectors. A second aspect is the infrastructure required for largescale, high-quality data collection. In Germany (outside the sector of Statistical Offices), this infrastructure is provided by private survey organisations. We argue that these should be recognised as relevant actors within the research data infrastructure. They have to invest in technological and human resources in order to provide the professional services required, and they need conditions and forms of cooperation that encourage this investment.
Keywords: 330; survey research; research infrastructure; Germany; quality; data collection; private public partnership